2020
DOI: 10.1101/2020.05.29.121954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic regulation of translation quality control associated with ribosome stalling

Abstract: Translation of problematic mRNA sequences induces ribosome stalling. Collided ribosomes at the stall site are recognized by cellular quality control machinery, resulting in dissociation of the ribosome from the mRNA and subsequent degradation of the nascent polypeptide and in some organisms, decay of the mRNA. However, the timing and regulation of these processes are unclear. We developed a SunTag-based reporter to monitor translation in real time on single mRNAs harboring difficult-to-translate poly(A) stretc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…smFISH Probe Labeling smFISH probes targeting the SunTag region of the mRNA reporter transcript were synthesized as described (39,40). 20-mer olgionucleotides were ordered from IDT in an arrayed format, pooled, and labeled on the 3'-end with amino-11-12 ddUTP (Lumiprobe A5040) using deoxynucleotidyl transferase (TdT, Thermo Fisher EP0162).…”
Section: Luciferase-based Real-time Translation Monitoring Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…smFISH Probe Labeling smFISH probes targeting the SunTag region of the mRNA reporter transcript were synthesized as described (39,40). 20-mer olgionucleotides were ordered from IDT in an arrayed format, pooled, and labeled on the 3'-end with amino-11-12 ddUTP (Lumiprobe A5040) using deoxynucleotidyl transferase (TdT, Thermo Fisher EP0162).…”
Section: Luciferase-based Real-time Translation Monitoring Assaymentioning
confidence: 99%
“…smFISH-IF was performed similarly as described (39,41). smFISH-IF was performed on cell stably expressing the SunTag mRNA reporter and scFV-sfGFP.…”
Section: Smfish-ifmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies on the global analysis of disome formation suggested that collisions are relatively common, and most of these events are resolved without translation termination [29]. What determines whether a collision event will become a target of RQC or not is still an open question, but the disome structure, the time required to resume translation, and/or exposure of an empty A site, seem to play an important role in this decision [30].…”
Section: Introductionmentioning
confidence: 99%
“…smFISH Probe Labeling smFISH probes targeting the SunTag region of the mRNA reporter transcript were synthesized as described(41,42). 20-mer oligonucleotides (Supplementary table 1) were ordered from IDT in an arrayed format, pooled, and labeled on the 3'-end with amino-11-12 ddUTP (Lumiprobe A5040) using deoxynucleotidyl transferase (TdT, Thermo Fisher EP0162).…”
mentioning
confidence: 99%